The Current Issues of Indonesian EFL Students’ Writing Skills: Ability, Problem, and Reason in Writing Comparison and Contrast Essay - Toba, Rostanti; Noor, Widya Noviana; Sanu, La Ode (Dinamika Ilmu, 2019)
The aim of this study is to investigate issues of Indonesian EFL students’ writing skills, covering ability, problem and reason why they got problems in writing comparison and contrast essay. The convergent parallel of mixed methods was used to explore these issues by involving 52 EFL students of IAIN Samarinda who enrolled the academic essay writing course. The three research instruments; essay writing test, open-ended questionnaire and interview were used in the data collection. The findings of this study revealed that the Indonesian EFL students’ writing ability was good that categorized with the mean score 77.83. However, some of them encounter problems in writing aspects including content, organization, vocabulary, grammar, and mechanics. Their reasons in experiencing these problems are not only limited knowledge of writing aspects and comparison and contrast essay itself, but also they had own personal reasons; lack of writing practice, writing dislike, writing anxiety, negative writing perception, low writing motivation, insufficient time given in writing test, and also inadequate teaching writing process taught by their lecturers. Indeed, the teaching writing improvement that involved EFL students and lecturers should be well-integrated in order to alleviate the students’ essay writing problems related to their reasons and to improve their writing ability. Factors caused the writing difficulties will be discussed further and some suggestions will be given on this research.